Development and Validation of the Moral Injury Scales for Youth. Issue 3 (4th June 2019) - Chaplo, Shannon D.; Kerig, Patricia K.; Wainryb, Cecilia
Abstract: This paper describes the development and preliminary psychometric properties of the Moral Injury Scales for Youth (MISY). Although to date, the construct of moral injury has been focused on studies of samples of adult military personnel, the MISY was developed to extend the study of moral injury to interpersonal relationship stressors and transgressions among emerging adults, adolescents, and children. Participants in a validation study included 473 undergraduate students (78.6% female, age range: 18–25 years) recruited from a psychology participant pool at a large university in the Western United States as well as a second sample of 185 students recruited from the same pool, to assess reliability. Results of exploratory factor analysis and confirmatory factor analysis (CFA) indicated that the MISY demonstrated a five‐factor latent structure with good internal consistencies. Correlational analyses indicated that the MISY subscales demonstrated good convergent validity, divergent validity, and test–retest reliability. The findings suggest that the MISY is a psychometrically reliable and valid measure of moral injury in emerging adults, with utility for examining moral injury in nonmilitary youth populations. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Desarrollo y validación de la escala de daños morales para jóvenes ESCALA DE DAÑO MORAL PARA JÓVENES Este artículo describe el desarrollo y las propiedades psicométricas preliminares de la escala de daño moral para jóvenes (MIY en sus siglas en inglés). A pesar que a la fecha el concepto de daño moral se ha centrado en estudios de muestras de personal militar adulto, el MIY se desarrolló para ampliar el estudio del daño moral a factores de estrés interpersonales y transgresiones entre adultos emergentes, adolescentes y niños. Los participantes para el estudio de validación incluyeron a 473 estudiantes de pregrado (78.6% mujeres, rango de edad: 18 a 25 años) reclutados de un grupo de participantes de psicología en una universidad grande en el oeste de los Estados Unidos, así como una segunda muestra de 185 estudiantes reclutados del mismo grupo, para evaluar la fiabilidad. Los resultados del análisis factorial exploratorio y el análisis factorial confirmatorio (AFC) indicaron que el MIY demostró una estructura de cinco factores latentes con buena consistencia interna. Los análisis correlacionales indicaron que las subescalas de MIY demostraron una buena validez convergente, validez divergente y confiabilidad de test‐ retest. Los hallazgos sugieren que el MIY es una medida psicométricamente confiable y válida de daño moral en adultos emergentes, con utilidad para examinar daño moral en poblaciones no militares de jóvenes. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Development and Validation of the Moral Injury Scales for Youth Traditional Chinese 標題: 青少年道德創傷量表的發展和效度 撮要: 本文描述青少年道德創傷量表(MIY)的發展及初步的心理測量特性。目前為止, 對道德創傷的構念研究仍專注於成年軍事人口樣本, 而MIY的發展則旨在把對道德創傷的研究延伸至研究初成年人士、青少年及兒童的人際關係壓力源和犯罪行為。此驗證研究透過美國西部一所大型大學裡的心理學研究參與計劃, 招募了473名大學本科生(78.6%女性, 年齡值域: 18–25 歲)形成第一樣本;並在同一研究參與計劃中招募了185名學生作為第二樣本, 以評估可靠性。探索性因素分析及驗證性因素分析(CFA)結果顯示, MIY展現一個有五種因素的潛在結構並具有良好的內在一致性。相關分析反映, MIY的子量表展現良好的匯聚效度、鑑別效度及再測信度。結果顯示, MIY是對初成年人士的道德創傷可靠和有效的心理測量工具, 對於檢視軍隊以外的青少年人口其道德創傷亦有功用。 Simplified Chinese 标题: 青少年道德创伤量表的发展和效度 撮要: 本文描述青少年道德创伤量表(MIY)的发展及初步的心理测量特性。目前为止, 对道德创伤的构念研究仍专注于成年军事人口样本, 而MIY的发展则旨在把对道德创伤的研究延伸至研究初成年人士、青少年及儿童的人际关系压力源和犯罪行为。此验证研究透过美国西部一所大型大学里的心理学研究参与计划, 招募了473名大学本科生(78.6%女性, 年龄值域: 18–25 岁)形成第一样本;并在同一研究参与计划中招募了185名学生作为第二样本, 以评估可靠性。探索性因素分析及验证性因素分析(CFA)结果显示, MIY展现一个有五种因素的潜在结构并具有良好的内在一致性。相关分析反映, MIY的子量表展现良好的汇聚效度、鉴别效度及再测信度。结果显示, MIY是对初成年人士的道德创伤可靠和有效的心理测量工具, 对于检视军队以外的青少年人口其道德创伤亦有功用。